Associations between metabolic score for visceral fat and adult lung functions from NHANES 2007–2012 - Zhou, Jiacai; You, Linlin; Zhou, Xin; Li, Yuying (Frontiers in Nutrition, 2024)
Background Obesity is a significant part of the factors affecting lung function, and the assessment of obesity using the Metabolic Score for Visceral Fat (METS-VF) is more precise than other indicators like waist circumference and body mass index. This study investigated the relationship between lung function and METS-VF in The National Health and Nutrition Examination Survey (NHANES) database from 2007 to 2012. Method The data utilized in this study was obtained from National Health and Nutrition Examination Survey spanning the years 2007 to 2012. A multivariate linear regression analysis was employed to investigate the association between METS-VF and lung function, followed by subgroup analysis to identify populations that may exhibit heightened sensitivity. Nonlinear correlations were assessed by fitting a restricted cubic spline, with validation of results conducted via threshold effect analysis. Result In a study involving 4,356 participants, a weighted multiple linear regression model revealed a significant negative association between the METS-VF and forced expiratory volume in the first second (FEV1), forced vital capacity (FVC), FEV1/FVC ratio, and forced expiratory flow between 25 and 75% of FVC (FEF25-75%). However, no association was observed with peak expiratory flow rate (PEF). When dividing the METS-VF into thirds, participants in the highest third exhibited significantly decreased levels of FEV1 (β: −342, 95%CI: −440, −245, p < 0.001), FVC (β: −312, 95%CI: −431, −192, p < 0.001), FEV1/FVC (β: −0.020, 95%CI: −0.030, −0.010, p < 0.001), and FEF25-75% (β: −424, 95%CI: −562, −285, p < 0.001). However, there was no significant relationship with PEF (β: −89, 95%CI: −325, 147, p = 0.446). RCS curve indicated a nonlinear negative correlation between METS-VF and FEV1, FVC, and FEV1/FVC. For FEV1, a significant negative correlation was found when the METS-VF < 6.426 (β = −158.595, 95%CI: −228.183, −89.007). This negative association became more pronounced when the METS-VF > 6.426 (β = −314.548, 95%CI: −387.326, −241.770). For FVC, a negative association was observed when the METS-VF < 6.401, (β = −5.477, 95%CI: −91.655, 80.702), but it did not reach statistical significance. However, METS-VF > 6.401, METS VF and lung function show a significant negative correlation (β = −399.288, 95%CI: −486.187, −312.388). FEV1/FVC showed a negative correlation only before the inflection point (METS-VF < 6.263) (β = −0.040, 95%CI: −0.047, −0.032), after the inflection point (METS-VF > 6.263), no correlation was found, but there was no statistical significance (β = 0.000; 95%CI: −0.006, 0.007), and METS-VF had a linear negative correlation with FEF25-75%. Subgroup analysis showed that the association was consistent across a variety of demographic factors, including age, sex, race, hypertension, and coronary heart disease. In addition, we found a stronger association between men under 40 and lung function. Conclusion METS-VF showed a linear negative correlation with FEF25-75%, and a nonlinear negative correlation with FEV1, FVC, FEV1/FVC, and FEF25-75%, but was not associated with PEF, particularly among males under the age of 40. These findings offer valuable insights into managing lung function by controlling visceral fat.